2018
DOI: 10.18632/oncotarget.25695
|View full text |Cite
|
Sign up to set email alerts
|

Combined external beam radiotherapy with carbon ions and tumor targeting endoradiotherapy

Abstract: External beam radiotherapy (EBRT) with carbon ions and endoradiotherapy using radiolabeled tumor targeting agents are emerging concepts in precision cancer therapy. We report on combination effects of these two promising strategies.Tumor targeting 131I-labelled anti-EGFR-antibody (Cetuximab) was used in the prototypic EGFR-expressing A431 human squamous cell carcinoma xenograft model. A 131I-labelled melanin-binding benzamide derivative was utilized targeting B16F10 melanoma in an orthotopic syngeneic C57bl6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 67 publications
3
12
0
Order By: Relevance
“…Gene-expression analysis was performed as described [15,38] Gene transcripts with 30% or more non-assessable reads on the microarray were excluded from the analysis. Total norm intensity was performed on all samples.…”
Section: Analysis Of Gene Expression Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene-expression analysis was performed as described [15,38] Gene transcripts with 30% or more non-assessable reads on the microarray were excluded from the analysis. Total norm intensity was performed on all samples.…”
Section: Analysis Of Gene Expression Valuesmentioning
confidence: 99%
“…The gene expression data of irradiated HIO were normalized to the arithmetic mean values of the respective control-groups. To identify differentially regulated genes ANOVA, two-class unpaired t-test, and multiple testing correction (Bonferroni) was applied using the in-house developed Software (write out first time) SUMO, version 1.61j [38]. Hierarchical clustering using Manhatton distance (average sistance) was performed with SUMO.…”
Section: Analysis Of Gene Expression Valuesmentioning
confidence: 99%
“…Recently, the impact of scheduling of this type of combination on tumour response has been revisited by Corroyer et al, whose findings emphasized the importance of treatment scheduling according to pathophysiological criteria such as tumour vessel permeability and tumour growth kinetics for TRT-photon EBRT combinations [61]. Melzig et al found that combining the radiopharmaceuticals 131 I-Benzamide or 131 I-cetuximab with high LET carbon ion radiation increased their cytotoxic effects in in vivo models, B16F10 (melanoma) and A431 (skin epidermoid cancer), respectively [62]. The carbon ions activated the immune-response and the DNA damage and cell-cycle control pathways with marked enhancement of the effect of the TRT agents.…”
Section: Developments In Increasing Anticancer Potencymentioning
confidence: 99%
“…Along with the indirect immune modulating effects of PRT via induction of pro-immunogenic processes in tumor cells, CIRT (170 KeV/μm) has been shown to directly enhance phagocytic activity of murine macrophages as compared to 250 keV photon RT, while there was no difference between the effects of CIRT and photon RT on macrophage vitality [ 63 ]. Moreover, an enhanced immunogenic effect of CIRT was found to augment in vivo antibody-dependent cellular toxicity [ 222 , 223 ].…”
Section: Charged Particle Radiotherapymentioning
confidence: 99%